Addressing the Prominent Li+ Intercalation Process of Metal Sulfide Catalyst in Li‐S Batteries. Issue 6 (18th January 2022) - Wang, Jin; Yang, Shaohua; Xu, Zijia; Ai, Guo; Zhang, Ting; Mao, Wenfeng
Abstract: Various catalysts are adopted to boost the conversion chemistry of Lithium sulfur (Li‐S) batteries, but most of them are electrochemical‐active in a working Li‐S cell, and the changes of their chemical state and the induced influence toward the Li‐S catalytic mechanism are unclear. Herein, a dynamic catalytic mechanism is proposed by the selection of Li + ‐interaction‐reversible VS2 catalyst as a representative species to address this issue. The VS2 catalyst with ultrastable Li + intercalation/deintercalation characteristics, fast charge transport capability, and active capacity contribution can provide a strong and dynamic chemisorption toward polysulfide (LiPS). The resulting Li‐S batteries exhibit excellent cyclability at 3 C with capacity attenuation of 81.23% over 250 cycles and good rate capability up to 8 C. Moreover, a new insight toward the dynamic catalytic changes induced by the prominent Li + intercalation process of metal sulfide is proposed, which can provide more opportunities for the evolutional design for Li‐S catalysts. Abstract : VS2 is selected to address the Li + intercalation process of metal sulfide in Li‐S chemistry, and the dynamic catalytic mechanism of Lix VS2 is proposed: VS2 possesses Li + intercalation/deintercalation characteristics within the working window of Li‐S batteries; the lithiation‐active VS2 induces a strong affinity toward polysulfide, and both the affinity and the interface Li + charge transport capability tend to change during the lithiation process (VS2 →Li0.66 VS2 ).